Mathematics for economics and business - Jaques, Ian; Mathematical; Mathematics (New York: Financial Times Prentice Hall, 2009)
Covering the subject in an informal way, this book aims to demonstrate the relevance of mathematics as quickly and as painlessly as possible
Includes index
eng.
Keywords: Business mathematics Economics